Real improvement processes in the army based on the Lean Six Sigma concept - Epler, Igor J.; Božičković, Ranko C.; Arsić, Slaviša N.; Dinić, Jelena B. (Vojnotehnički glasnik / Military Technical Courier, 2015)
Readiness for challenge and change, doing more with less as well as focusing on quality and the customer - these are some of the most important areas of the activities of industrial producers, which military leaders in armies around the world have also developed to make their work more efficient and effective. This article provides an overview of the achievements in the United State of America (USA) military and its suppliers and associates, where the implementation of modern process management concepts has led to significant improvements and savings in various areas. The article also suggests possible applications of the existing successful business models in related areas in the Serbian Army.